Association Between Trauma from Occlusion and Periodontal Status of Mandibular Anterior Teeth - R, HARIPRIYA.; RAJASEKAR, ARVINA; B, NIVETHIGAA. (The journal of contemporary issues in business and government, 2021)
Any occlusal force which goes beyond the adaptive capacity of our periodontium causes injury to periodontal structure, and the resultant trauma is called trauma from occlusion (TFO). Several views have been interpreted as trauma from occlusion as an etiological factor or cofactor for occurrence of periodontal status. The aim of the present study was to assess the association between trauma from occlusion and mandibular anterior teeth. This retrospective study was conducted in a private institution in Chennai using the patient records from June 2019 to March 2020. A total of 100 patients were randomly selected and were categorized into two groups; Group 1 (n=50): patients with TFO and Group 2 (n=50): patients without TFO. Data regarding the presence or absence of clinical attachment loss and mobility of mandibular anterior teeth was collected from the record and analysed. Descriptive and inferential statistics were done using SPSS software, Version 23. In the present study, majority of the patients with trauma from occlusion presented with clinical attachment loss (43%) and mobility in mandibular anterior teeth (38%). Also, there was a statistically significant association between trauma from occlusion and periodontal disease in mandibular anterior teeth. (p=0.000)